Strategic Orientation of Transportation in Slovenia - Trupac, Igor (Promet - Traffic&Transportation)
The paper deals with strategic goals and decisions to betaken for the integration of Slovenia into the European Union.One of the most important factors of this integration is transportation.This process should not be chaotic or driven by blindforces but carefully and strategically orientated in the macroand the micro field.The paper also suggests general strategy of transportation,defines goals, measures to be taken and identifies authorities.